2008
DOI: 10.1021/nl801396r
|View full text |Cite
|
Sign up to set email alerts
|

Direct Near-Field Optical Imaging of Higher Order Plasmonic Resonances

Abstract: We map in real space and by purely optical means near-field optical information of localized surface plasmon polariton (LSPP) resonances excited in nanoscopic particles. We demonstrate that careful polarization control enables apertureless scanning near-field optical microscopy (aSNOM) to image dipolar and quadrupolar LSPPs of the bare sample with high fidelity in both amplitude and phase. This establishes a routine method for in situ optical microscopy of plasmonic and other resonant structures under ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
207
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(212 citation statements)
references
References 31 publications
4
207
1
Order By: Relevance
“…We also observed that the light intensity rapidly decays in the vertical direction above the structure, showing a strong nearfield localization. In contrast to experiments performed with fiber-type probes [21][22][23][24] or scattering tips, 19,20 our measurements directly represent the intensity of the total field located on the surface (or more precisely, the square of the total field intensity). They indicate, in three dimensions, the zones of the structure that would be active if we use it as a chemical sensor or for performing near-field nanolithography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that the light intensity rapidly decays in the vertical direction above the structure, showing a strong nearfield localization. In contrast to experiments performed with fiber-type probes [21][22][23][24] or scattering tips, 19,20 our measurements directly represent the intensity of the total field located on the surface (or more precisely, the square of the total field intensity). They indicate, in three dimensions, the zones of the structure that would be active if we use it as a chemical sensor or for performing near-field nanolithography.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, our aim is to directly observe the electromagnetic field distribution using a scanning near-field optical microscope (SNOM). Recently, many SNOM experiments have been performed on isolated or coupled nanostructures, [17][18][19][20] but only very few studies have been achieved on arrays. Salerno et al 21 and Salomon et al 22 observed the localization of light on an array of gold nanoparticles with a SNOM, but the structures were separated from each other by one micrometer, which makes them almost isolated from each other.…”
Section: Introductionmentioning
confidence: 99%
“…19͒ has managed to map both the local amplitude and phase of the plasmon modes by interferometric detection of the antenna fields scattered by a scanning atomic force microscope tip. [20][21][22][23][24] However, the antenna optical response is extremely sensitive to environmental changes, 5,8,9 thus the process of measurement of its near field may result in the modification of the antenna modes, similar to probe-induced modifications in other nanophotonic systems. [25][26][27][28] In this work we address this issue, presenting a basic understanding of the near-field coupling between s-SNOM probes and plasmonic nanoantennas ͑here gold nanodisks͒.…”
mentioning
confidence: 99%
“…[43][44][45][46] To push the spatial resolution down to less than 10 nm, apertureless SNOM (aSNOM or aNSOM) uses point-or needlelike probes, whose apex radius largely determines the achievable lateral resolution, 47 essentially independent of wavelength. aSNOM is increasingly being applied to individual nano-plasmonic structures like disks, 13,23 holes, 48 triangles, 49 linear wireantennas 14,50-52 ( Fig. 2).…”
Section: Nearfield Optical Techniquesmentioning
confidence: 99%
“…Ad hoc, this is verified by the favourable comparison with simulations of the bare sample in the absence of any probe. 13,14,51 3. Photon-in/electron-out methods Photoemission (PE) of electrons (or ''photo-electric effect'') is not only one of the pillars of quantum-physics.…”
Section: Nearfield Optical Techniquesmentioning
confidence: 99%